The pathophysiology, incidence, impact, and treatment of opioid‐induced nausea and vomiting. Issue 11 (13th November 2017) - Mallick‐Searle, Theresa; Fillman, Mechele
Abstract: Purpose: Opioid medications are integral in managing acute moderate‐to‐severe pain. Opioid analgesics bind to μ (mu), κ (kappa), or δ (delta) opioid receptors in the brain, spinal cord, and digestive tract. However, opioids cause adverse effects that may interfere with their therapeutic use. Some adverse effects wane over time, but patients using opioids for acute pain struggle with opioid‐induced nausea and vomiting (OINV) the entire time they take the opioid. This article discusses the underlying mechanisms, clinical implications, and treatment strategies of OINV. Data sources: Systematic search and review of Medline, PubMed, and Google Scholar for articles relating to OINV. In addition, package inserts provided pharmacologic data and dose recommendations as needed. Conclusions: Research suggests approximately 40% of patients may experience nausea and 15%–25% of patients may experience vomiting after opioid administration. Nausea often precedes vomiting, although they can occur separately. Many patients receiving opioids rate the nausea and vomiting as worse than their pain. Nausea and vomiting can lead to complications including electrolyte imbalances, malnutrition, and volume depletion, and can also negatively affect quality of life and postoperative recovery. Implications for practice: There are several medications that can be used to treat OINV including serotonin receptor antagonists, dopamine receptor antagonists, and neurokinin‐1 receptor antagonists. Healthcare providers should be proactive about discussing OINV with patients, as this may improve patient outcomes and pain relief.